PEMANFAATAN MOBILE EDUKASI SEBAGAI STRATEGI BELAJAR PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM - Budiana Budiana (Jurnal Didaktika Pendidikan Dasar, 2019)
The development of mobile education is the right step in the midst of rapid advances in technology, information, and communication. The smartphone is one of the information technology products that become a trend among students. It is unfortunate if the sophistication of this technology is only used as a means of communication and as social media alone. Opportunities and great potential for teachers to use smartphones as multi-interactive learning media with high flexibility as a student learning strategy. This research employing the concept of development aims to produce mobile education products, to know the level of feasibility as a learning media, and to find out its effectiveness as a student learning strategy. From the results of the analysis and trials of students and teachers, it is known that the mobile education application has met the feasibility standard as a learning medium, the presentation of the material, and the effectiveness of its use in learning are also considered feasible. The product is implemented in Grade 9H students on the material of laudable behavior. The use of mobile education as a learning tool for students in the material of laudable behavior in the subjects of Islamic Education and Character has proven to be effective in supporting learning outcomes.